Transcaucasia at the End of the Early Bronze Age - Edens, Christopher (1995)
Transcaucasia was the heartland of the Kura-Araxes, or Early Transcaucasian culture, which holds an important place in the culture history of eastern Anatolia. The transition from this Early Bronze Age culture to the more fragmented regional cultures of the Middle Bronze Age remains poorly defined. The transition is marked by a shift away from fairly autonomous village life, the appearance of evidence for enhanced social hierarchy, and the first use of tin-bronzes in Transcaucasia. Traditional chronology places the transition at the end of the third millennium B. C. However, radiocarbon evidence indicates a mid-third millennium date for the transitional cultures, thus aligning Transcaucasian developments more closely with those in eastern Anatolia and northwestern Iran (late Early Bronze Age) and in Ciscaucasia (Maikop). Transcaucasia seems to have continued to play an important interregional role even after the disappearance of the Kura-Araxes cultures.